Fabrication and characterization of nanopatterns for selective cell adhesion - Park, Soyeun (Journal of the Korean Physical Society, 2015)
Nanopatterns with chemical functionalization are of importance in biological sensing and drug delivery systems. Despite recent advances in nanotechnology, producing large-area nanopatterned surfaces for controlling the size of cellular adhesion sites is still a challenge. Unlike for homogeneous substrates, only a few techniques suitable for characterizing the chemical properties of nanopatterned substrates with a sufficient lateral resolution exist. In this research, we fabricated nanopatterned substrates composed of 2D arrays of gold nanoislands by using nanosphere lithography (NSL). Orthogonal chemistry was applied to achieve a selective adsorption of fibronectins to nanoislands. The contact angle and the X-ray photoelectron spectroscopy (XPS) data confirmed the success of the dual functionalization performed on 1/2Au-1/2glass substrates. The chemical properties of nanopatterns were investigated by using Atomic Force Microscopy (AFM). The adhesion maps and the topographic images confirmed nanometer-scale chemical functionalization.